2016
DOI: 10.1590/1413-81232015219.17362016
|View full text |Cite
|
Sign up to set email alerts
|

A contribuição do Programa Mais Médicos: análise a partir das recomendações da OMS para provimento de médicos

Abstract: In order to examine whether Brazil's Mais Médicos (More Doctors)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
0
15
1
13
Order By: Relevance
“…In this respect, our findings disagree in part with those of Carvalho et al 59 , who assessed the Programa Mais Médicos against WHO recommendations and concluded that the program was successful in only 37.5% of the 16 recommendations. It should be noted, however, that a number of these recommendations, such as improvements in rural infrastructure, were outside the scope of the initiative, thus affecting its performance.…”
Section: Discussioncontrasting
confidence: 99%
“…In this respect, our findings disagree in part with those of Carvalho et al 59 , who assessed the Programa Mais Médicos against WHO recommendations and concluded that the program was successful in only 37.5% of the 16 recommendations. It should be noted, however, that a number of these recommendations, such as improvements in rural infrastructure, were outside the scope of the initiative, thus affecting its performance.…”
Section: Discussioncontrasting
confidence: 99%
“…The migration of doctors from ESF teams to the PMM vacancies is especially worrying. For several years, the competition for doctors has been part of the daily challenges faced by municipal health secretariats in Brazil (28). The municipalities cannot compete with the federal government regarding salary conditions due to restrictions imposed by a Brazilian law of fiscal responsibility (27) that sets an upper limit on salaries for each level of public administration.…”
Section: Discussionmentioning
confidence: 99%
“…The PMM is the initiative that has had the best results in terms of attracting physicians to remote and disadvantaged areas and keeping them there (28). An abrupt change in the logic of the program might have consequences for the health needs of the Rev Panam Salud Publica 44, 2020 | www.paho.org/journal | https://doi.org/10.26633/RPSP.2020.31…”
Section: Discussionmentioning
confidence: 99%
“…8 A contemporary health model for older adults needs to bring together the flux of health education, health promotion, the prevention of preventable diseases, the delayed onset of diseases, early care and disease rehabilitation. A line of care 9 for older adults which seeks to be effective and efficient should presuppose an articulated, referenced network, with an information system designed in keeping with this logic. We live in the age of technology and information.…”
Section: Impact and Relevance Of The Workmentioning
confidence: 99%